2021
DOI: 10.3389/fnagi.2020.625166
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation Increases the Susceptibility to Levodopa-Induced Dyskinesia in 6-OHDA Lesioned Rats by Targeting the NR2B-Medicated PKC/MEK/ERK Pathway

Abstract: Background: The long-term administration of levodopa (L-dopa), the gold-standard treatment for Parkinson's disease (PD), is irreparably associated with L-dopa-induced dyskinesia (LID), which dramatically affects the quality of life of patients. However, the underlying molecular mechanisms of how LID exacerbates remain unknown. Neuroinflammation in the striatum plays an active role in LID. These findings prompt an investigation of non-neuronal mechanisms of LID. This study will examine the effects of systemic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 48 publications
5
23
0
Order By: Relevance
“…IL-1β was reported to activate the cortical neurons through the ionotropic glutamate receptor (N-methyl-D-aspartic acid receptor 2B, NR2B), mediating the downstream signaling pathway ( Davis et al, 2006 ). Our recent study further confirmed that the expression level of TNF-α and IL-1 β positively correlated with the neuron membrane-expressed NR2B receptor-mediated ERK1/2 phosphorylation and the intensity of LID ( Yan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…IL-1β was reported to activate the cortical neurons through the ionotropic glutamate receptor (N-methyl-D-aspartic acid receptor 2B, NR2B), mediating the downstream signaling pathway ( Davis et al, 2006 ). Our recent study further confirmed that the expression level of TNF-α and IL-1 β positively correlated with the neuron membrane-expressed NR2B receptor-mediated ERK1/2 phosphorylation and the intensity of LID ( Yan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 75%
“…A recent study reported that intermittent L-dopa administration induced an enhanced neuroinflammation response in the striatum, compared to continuous L-dopa delivery ( Mulas et al, 2016 ). Our recent study reported that the dyskinetic movement severity was significantly exacerbated when the striatal neuroinflammation response was enhanced by a systemic inflammatory stimulus of LPS prior to intermittent L-dopa administration ( Yan et al, 2021 ). By contrast, the dyskinetic movements were greatly reduced in the PD model where the striatal neuroinflammation response was inhibited by a systemic administration of corticosterone prior to intermittent L-dopa stimulation ( Barnum et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…18 Previous studies suggest that systemic inflammatory stimulation exacerbates AIM induced by levodopa treatment in MPTP lesioned mice and increases pro-inflammatory cytokines in the striatum of LID mice. 1,2 In our MPTP-induced PD model, infiltration of inflammatory cells was found in the parenchymal striatum in the levodopa group, which is in accordance with previous studies showing that neuroinflammation could exacerbate levodopa-induced dyskinesia. 19 Inflammation has a pathogenic role in neurodegenerative diseases.…”
supporting
confidence: 91%
“…Dyskinesia (abnormal involuntary movements) has also been shown to affect a majority of PD patients receiving levodopa, which limits its clinical application. 2 Aging is considered a primary risk factor for the development of PD. Aging-related neuroinflammation has been shown to lead to neuronal loss.…”
Section: Introductionmentioning
confidence: 99%
“…Possibly actin cytoskeleton passed the force to trigger the ER Ca 2+ signals ( Kim et al, 2015 ), which is also suggested from our data ( Figures 5A–E ). Ca 2+ signals can further activate PKC to induce Ras-Raf-MEK-ERK pathway ( Liao et al, 2020 ; Yan et al, 2020 ), and our data showed that inhibition of Ras truly blocked the mechanical activation of ERK ( Figures 5D,E ). These data indicate that actin cytoskeleton belongs to the mechanosensing component for ERK activation.…”
Section: Discussionmentioning
confidence: 57%